An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae) - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zootaxa, 2015)
In the present study, a catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae) is given. It is based on a detailed study of all available published data. In total 78 species from 15 genera including Alloea Haliday, 1833 (1 species), Angelovia Zaykov, 1980 (1 species), Aphaereta Foerster, 1862 (2 species), Aspilota Foerster, 1862 (2 species), Chorebus Haliday, 1833 (42 species), Coelinidea Viereck, 1913 (2 species), Coloneura Foerster, 1862 (1 species), Dacnusa Haliday, 1833 (10 species), Dinotrema Foerster, 1862 (5 species), Idiasta Foerster, 1862 (1 species), Orthostigma Ratzeburg, 1844 (3 species), Phaenocarpa Foerster, 1862 (1 species), Protodacnusa Griffiths, 1964 (2 species), Pseudopezomachus Mantero, 1905 (2 species), and Synaldis Foerster, 1862 (3 species) are reported in this catalogue. Two species are new records for Iran: Coelinidea elegans (Curtis, 1829) and Dacnusa (Pachysema) aterrima Thomson, 1895. Also, a faunistic list with distribution data and host records is provided.